2020
DOI: 10.3390/su12062514
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences and Influential Factors of Open Public Space in Chinese Cities Based on Big Earth Data

Abstract: Urban open public spaces that provide multiple services for residents are essential for improving life quality and urban ecosystem function and promoting healthy development, the safety of human settlements and the sustainable development of urban cities. Based on Sustainable Development Goal 11.7 of the United Nations (UN) 2030 Agenda, this study combines the big earth data with the Theil index, a coefficient of variation and Exploratory Spatial Data Analysis (ESDA) to analyze the regional differences and spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This product has helped to resolve a data deficiency in long-term urban expansion time-series datasets for 1,500 cities with populations greater than 300,000 in the Belt and Road region, produced from 1990 to 2015 at five-year intervals (Li, Cai, & Du, 2021). Case studies related to SDG 11.3.1 and 11.7.1 used Big Earth Data techniques and found that the expansion of urban built-up areas began to slow down after 2015 while open public space as a proportion of built-up areas in 342 prefectural cities increased by 1.5% on average (Wang, Huang, Feng, Zhao, & Gu, 2020c;Wang et al, 2020b). Public access to transportation was observed to have increased in approximately 80% of cities to varying degrees.…”
Section: Efforts Towards Utilizing Big Earth Data For Sdgsmentioning
confidence: 99%
“…This product has helped to resolve a data deficiency in long-term urban expansion time-series datasets for 1,500 cities with populations greater than 300,000 in the Belt and Road region, produced from 1990 to 2015 at five-year intervals (Li, Cai, & Du, 2021). Case studies related to SDG 11.3.1 and 11.7.1 used Big Earth Data techniques and found that the expansion of urban built-up areas began to slow down after 2015 while open public space as a proportion of built-up areas in 342 prefectural cities increased by 1.5% on average (Wang, Huang, Feng, Zhao, & Gu, 2020c;Wang et al, 2020b). Public access to transportation was observed to have increased in approximately 80% of cities to varying degrees.…”
Section: Efforts Towards Utilizing Big Earth Data For Sdgsmentioning
confidence: 99%